2013
DOI: 10.1186/1471-2458-13-2
|View full text |Cite
|
Sign up to set email alerts
|

Repository on maternal child health: Health portal to improve access to information on maternal child health in India

Abstract: BackgroundQuality and essential health information is considered one of the most cost-effective interventions to improve health for a developing country. Healthcare portals have revolutionalized access to health information and knowledge using the Internet and related technologies, but their usage is far from satisfactory in India. This article describes a health portal developed in India aimed at providing one-stop access to efficiently search, organize and share maternal child health information relevant fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 10 publications
2
42
0
1
Order By: Relevance
“…[44], Karimi et al [45]Social DistancingPoletti et al . [46], Mummert & Weiss [47], Zhong et al [48]Larson & Nigmatulina [49], Wang [50], Greer [51], Morin et al . [52], Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…[44], Karimi et al [45]Social DistancingPoletti et al . [46], Mummert & Weiss [47], Zhong et al [48]Larson & Nigmatulina [49], Wang [50], Greer [51], Morin et al . [52], Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…1 st trimester (weeks 1-12), 2 nd trimester (weeks 13-28) and 3 rd trimester (weeks 29-40). For the purpose of depiction in our application, we identified each target division with the associated medical tests, signs and symptoms, the possible problems and complications that may arise, the prescribed medication and diet, and healthy practices and precautionary measures [7,[13][14][15]28]. In this manner, we determined the information architecture that the medical data in our ICT would subscribe to.…”
Section: Abstracting Background Medical Datamentioning
confidence: 99%
“…Khanna et al [23] were the only authors to specifically use the criteria by Lee et al [11] and Goh et al [13] to conduct a ‘quality assessment’ of a portal in regards to features supporting knowledge management. Their assessment revealed that the maternal child health portal contained many features to support knowledge access, but not knowledge creation (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…related to chronic disease prevention [22], cancer prevention or control [26] and maternal and child health [23]. Maintaining the credibility, reliability and level of evidence accessible through these portals is particularly important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation